Project-based Learning an Innovation in Teaching RELT: A Study on Students’ Needs - Harida, Eka Sustri; Siregar, Fitri Rayani; Siregar, Sri Rahmadhani; Ritonga, Arini Bulan; Nasution, Riandry Fadhilah (AT-TA'LIM, 2023)
The condition of learning in the post-pandemic era varies; although the learning process can be fully offline, some universities do blended learning. A blended learning system also happened in UIN Syahada Padangsidimpuan. This paper aims to inform the needs of students in learning research in ELT subjects; it was one of the subjects distributed to English students at this university. The data were taken using mixed-method methods, and the data was collected using questionnaires and interviews. 61 (sixty-one) students filled out the questionnaires, and 10 (ten) students were asked to get interviews. The data were analyzed quantitatively and qualitatively. After analyzing the data, it was found that the students liked to study using several methods. Although they have been stated to study with several methods, the highest percentage is Project-based Learning (PjBL). Based on the result, it can be concluded that the students need the PjBL in learning Research in English Language Teaching (RELT) subject matter. The students agreed that this learning method could prepare them to write a final task in their study